Sequence, gaze, and modal semantics: modal verb selection in German permission inquiries - Zinken Jörg; Mack Christina (Linguistics)
Two modal verbs of German are regularly used to express deontic possibility: können (‘can’) and dürfen (‘may’). We examine how speakers select between them, focusing on modal inquiries for permission to carry out some action (darf/kann ich das machen, ‘may/can I do this’). Our data are video-recordings of everyday face-to-face interaction, which we analyze sequentially, drawing on interactional-linguistic methods. We find that local sequential context and aspects of visible turn-design systematically enter into the accomplishment of deontic meaning. (1) Position of the modal inquiry within a course of action informs verb selection: speakers select kann to nominate an action as coming “out of the blue” and initiating a new course of action; darf to nominate an action as sequentially occasioned: a solution to an already known-in-common problem. (2) Bodily behavior (gaze, body posture) guides the interpretation of modal flavor, moving a kann-inquiry towards a deontic or a circumstantial interpretation, and moving a darf-inquiry towards a deontic or a bouletic interpretation. Overall, the study demonstrates the systematic contributions of sequential position and body behavior in the accomplishment of modal meanings.